Influence of the kind and age of the inoculum on the development of rot caused by Penicillium expansum (Link) Thom on stored apples - H. Borecka; H. Bryk (Acta Agrobotanica, 2013)
The influence of the kind and age of the inoculum on development of rot on 'Bankroft' and 'Mcintosh' apples was tested. The inoculum consisted of spore suspension and disks of culture of Penicillium expansum (Link) Thorn. Spores were taken from cultures 3, 7, 14, 28 and 52 days old. Disks were prepared from 3- and 7-day-old cultures. The mother cultures in both cases were inoculated with spore suspensione from 7-day-old culture. The influence of the kind and age of cultures was significant, particularly after longer storage period. The rot developed faster after inoculation with the disks of culture than with the spore suspension. The speed of rot development on the four cvs of apples was compared; the rot developed fastest on 'Mcintosh'.